(3fgGjI GdSDd hGdCefjI aj JYde CYeGd GdaQhSjIs - (3fLe GdOjf GdCMOH (B: (3eMeO Hf YjSi Hf ESeGYjd GdMfajs ((3OeTb s)
(3ChdgG (B:s
(3hHYO aEfi de CRd HYO eG hgH Gddg di ef GdeYQag HBdGJ GdaQhSjI eG hgH s
(3BNQgG (B:s
(3JDNP fhQg hJTO ai NQbI QbjbI hjJMQc ai EfGA ajg eGA MJi jNQL eG ajg ef GdfhQ hjHbi GdJfbd s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B136 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B37 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1988s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CMeO GdKGdK HGSJGfHhd (B(2651) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs